Powtoon: Does It Promote Primary Students’ Autonomous Learning? - Suprianti, G.A.P.; Budiarta, Luh Gd Rahayu; Indrayani, Luh (UNIB Press, 2024)
Implementing appropriate teaching media results in effective teaching and promote students to be more responsible for their learning through autonomous learning. This study aimed (1) to discover a significant difference between the students who learned by using PowToon videos and those by YouTube videos; (2) to investigate the responses of the students learned autonomously by using PowToon video. This research employed Explanatory Sequential Mixed Method Design consisted of quantitative and qualitative data obtained at a private kindergarten in Singaraja. The data were gained through post-test, interview, and questionnaire. The results showed that there was a significant difference between students who used PowToon and those by YouTube since the former average score reached 91.67. According to the result of interview and questionnaire, it was found good responses from the students and could help them learn English with greater passion and autonomously. Thus, utilizing proper media lead to the students’ independent learning.